1990
DOI: 10.1136/thx.45.5.382
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of airborne moulds in the homes of children with and without wheeze.

Abstract: A population survey of 1000 7 year old children found a significant excess of wheeze among children whose homes were reported to be mouldy (odds ratio 3 70, 95% confidence limits 2-22, 6-15).The airborne mould flora was quantified by repeated volumetric sampling during the winter in three rooms of the homes of 88 children. All of these had previously completed spirometric tests before and after a six minute free running exercise challenge. Total airborne mould counts varied from 0 to 41 000 colony forming unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
78
4
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(92 citation statements)
references
References 17 publications
8
78
4
2
Order By: Relevance
“…Results have shown null, weak, and significant positive associations among the two exposure types as well as inconsistencies across studies with respect to the taxa showing associations with home characteristics (Waegemaekers et al, 1989;Strachan et al, 1990;Wickman et al, 1992;Li and Hsu, 1997;Garrett et al, 1998;Ren et al, 2001;Chew et al, 2003;O'Connor et al, 2004). These inconsistencies could be secondary to geographic location, season of sampling, as well as housing types and construction materials.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Results have shown null, weak, and significant positive associations among the two exposure types as well as inconsistencies across studies with respect to the taxa showing associations with home characteristics (Waegemaekers et al, 1989;Strachan et al, 1990;Wickman et al, 1992;Li and Hsu, 1997;Garrett et al, 1998;Ren et al, 2001;Chew et al, 2003;O'Connor et al, 2004). These inconsistencies could be secondary to geographic location, season of sampling, as well as housing types and construction materials.…”
Section: Discussionmentioning
confidence: 95%
“…Numerous studies (primarily cross-sectional in design) involving older children and adults have reported at least one positive association between total airborne fungal or bacterial counts, or specific fungal taxa including Penicillium, Cladosporium, Aspergillus or Alternaria species, and respiratory symptoms including cough, wheeze and asthma (Platt et al, 1989;Strachan et al, 1990;Bjornsson et al, 1995;Li and Hsu, 1997;Garrett et al, 1998;Dharmage et al, 2001;Downs et al, 2001). Null findings in all age groups also have been reported for both airborne (Su et al, 2001) and dustborne fungi (Wickman et al, 1992;Verhoeff et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…(22) Generally, air sampling has been a commonly used method to assess fungal exposure and has also been described as the most representative of human respiratory exposure. (35,(72)(73)(74)(75)(76) However, this study has demonstrated that short-term air sampling may not be an indicative measure of mold contamination in the indoor environment, as the number of spores released by the source (FSSST) did not relate to the airborne spore concentration. This was the case even though the indoor mold contamination levels were approximately an order of magnitude higher than the outdoor levels.…”
Section: Discussionmentioning
confidence: 99%
“…(3,33,34) Furthermore, some health effects, especially respiratory allergies, have been shown to be associated with the total spore count rather than with the CFU count. (33,35) Similar to the CFU count, there are some advantages and disadvantages of the total spore count method. Two advantages are that (1) both viable and nonviable spores can be included, and (2) the total count is less time-consuming than the CFU analysis (can be performed within hours of sample collection).…”
mentioning
confidence: 99%
“…However, attempts to correlate health outcomes with spore counts have not indicated strong associations. Furthermore, several field studies have shown that the concentrations of airborne fungal spores in mold problem buildings are not necessarily higher than in non-problem ones (Strachan et al, 1990;Nevalainen et al, 1991;Garrett et al, 1998;Chew et al, 2003). This indicates that spore concentrations may not be an adequate measure for fungal exposures.…”
Section: Introductionmentioning
confidence: 99%